Mechanism for Improving Acid-Induced Hazelnut Protein Gels Through High-Pressure Homogenization: Effect on Structural, Rheological and Gelling Properties - Gul, Osman; Akgun, Abdullah; Maribao, Iannie P.; Parlak, Mahmut Ekrem; Saricaoglu, Furkan Turker; Simsek, Senay (Mdpi, 2025)
This study aimed to investigate the effects of high-pressure homogenization (HPH) (0, 25, 50, 100, and 150 MPa) pretreatment on the structural, rheological, and gelling properties of alkaline-extracted hazelnut protein isolate gels induced by glucono-delta-lactone (GDL). Homogenization pretreatment shortened the time required to obtain the maximum G ' value (12.65 Pa) from 32 to 28 min in the control sample. The particle size of protein isolates decreased with increasing pressure, resulting in lower particle size aggregates after gelation and in a denser gel structure with increasing gel hardness (from 1.52 g to 2.06 g) and WHC (from 31.95% to 48.36%). FT-IR spectroscopy revealed that HPH pretreatment and gelling time changed the secondary structure of the protein, promoting the formation of hazelnut protein gels. Hazelnut gel pretreated at 150 MPa exhibited the highest apparent viscosity and G ' value, indicating a more elastic and stronger gel network structure. The gel intermolecular force results showed that the contribution of hydrophobic interactions to gel formation was significant, and the chemical bond content of the gels increased with the increase in pressure up to 100 MPa. The physical stability of the gels was also improved by HPH pretreatment. Although the best WHC and physical stability were observed in the 100 MPa-pretreated gel sample, the hazelnut protein isolate pretreated at 150 MPa exhibited the best gel performance. Overall, HPH pretreatment has the potential to enhance hazelnut protein gel properties for industrial food applications.
Keywords: hazelnut protein; high-pressure homogenization; acid-induced gelation; rheology; intermolecular forces; structure